WISC-V motor-free cognitive profile and predictive factors in adolescents with cerebral palsy. (June 2021) - Coceski, Monika; Hocking, Darren R.; Abu-Rayya, Hisham M.; Sherwell, Sarah; Reid, Susan M.; Reddihough, Dinah S.; Wrennall, Jacquie; Stargatt, Robyn
Highlights: Cognitive profile of adolescents with cerebral palsy was characterized using motor-free WISC-V. Motor-free IQ scores of adolescents with cerebral palsy fell below age expectations. Adolescents with cerebral palsy show relative strength in verbal intelligence. Poor cognition linked to severity of motor impairment and small for gestational age. Rates of borderline cognitive ability are higher than expected in adolescents with cerebral palsy. Abstract: Background: The most commonly used intelligence tests – the Wechsler Scales – do not provide standardised procedures for assessing children with motor impairment, and as a result, may underestimate the intelligence quotient (IQ) of young people with CP. Aims: To characterise a motor-free cognitive profile of adolescents with CP using the Wechsler Intelligence Scale for Children – Fifth edition (WISC-V) and explore the influence of clinical factors on cognitive abilities. Methods and procedure: The WISC-V was used to assess cognitive abilities in 70 adolescents ( M = 14 years 6 months, SD = 10 months). Sixty-six adolescents (Gross Motor Function Classification System (GMFCS) Level I, n = 26 ; II, n = 23; III, n = 15; IV, n = 1; V, n = 1) obtained either a Motor-free IQ or index score using the motor-free method. Outcomes and results: MFIQ and index scores fell below the normative data and rates of borderline and impaired cognitive abilities were significantly higher in the CP group. Scores showed an uneven cognitive profile with a relative strength in verbal abilities. Severity of motor impairment and small for gestational age (SGA) were associated with lower IQ scores. A history of seizures was related to lower verbal abilities. Conclusions and implications: Cognitive abilities of adolescents with CP are significantly below expectation compared to normative data. Severity of motor impairment, SGA, and seizures need to be recognised by health professionals as risk factors for cognitive impairment. A substantial proportion of adolescents showed borderline cognitive abilities, constituting a group with CP which are relatively neglected in the literature.